Faktor-faktor yang berhubungan dengan hardiness perawat di rumah sakit: A literature review - Syafni, Syafni; Bayhakki, Bayhakki; Lestari, Widia (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Hardiness or mental resilience is an individual's ability to manage, overcome, reduce and survive stress or unpleasant conditions in life. The task of nurses in nursing practice is to provide nursing care to overcome both physical and psychological problems of patients, requiring a strong nurse personality and good work resilience. Purpose: To determine the factors associated with the hardiness of nurses working in hospitals. Method: Literature review research uses the PICO (Population/problem) method in searching for articles. The inclusion criteria for articles were that they were published in 2019-2023, had full text available, in Indonesian or English, and used quantitative or qualitative research methods carried out on nurses working in hospitals. The keywords used for the search were